The value of the oral glucose tolerance test, random serum growth hormone and mean growth hormone levels in assessing the postoperative outcome of patients with acromegaly. - Karavitaki, N; Fernandez, A; Fazal-Sanderson, V; Wass, J (2009)
BACKGROUND: The nadir GH value following an oral glucose tolerance test (OGTT) and the mean GH levels obtained from a GH day curve (GHDC) are among the tools currently used for assessing therapeutic end-points in surgically treated acromegaly. The latter test, however, is cumbersome and costly. OBJECTIVES: To evaluate, by using a modern, two-site chemiluminescent immunometric GH assay, the degree of discordance between the nadir GH following an OGTT and the mean GH obtained from a GHDC after surgical treatment of acromegaly and to check whether the OGTT can replace reliably the GHDC for the assessment of the disease status postoperatively. PATIENTS AND METHODS: Forty-nine patients [25 males/24 females, median age 52 years (range 18-70)] with a GH-secreting pituitary adenoma who had been surgically treated previously underwent hormonal evaluation of their disease status. The GHDC comprised of 9 x 30-min samples for GH collected in the morning after an overnight fast and rest. RESULTS: Seven per cent of patients with mean GH <1.7 mug/l (5 mU/l) in the GHDC had nadir GH >0.7 mug/l (2 mU/l) in the OGTT, and 10% of those with mean GH >1.7 mug/l had nadir GH <0.7 mug/l in the OGTT (all cases with discrepancies had normal IGF-I). GH value at time 0 min <0.6 mug/l in the OGTT had positive predictive value 100% and negative predictive value 75% in predicting nadir GH <0.3 mug/l (1 mU/l) in the OGTT. Nadir GH <0.8 mug/l in the OGTT had positive predictive value 97% and negative predictive value 95% in predicting mean GH <1.7 mug/l in the GHDC. Mean GH in the OGTT <1.4 mug/l had a positive predictive value 90% and negative predictive value 95% in predicting mean GH <1.7 mug/l in the GHDC. Mean GH in the OGTT <2.5 mug/l had positive predictive value 100% and negative predictive value 81% in predicting normal IGF-I. GH at time 0 min in the GHDC <2.1 mug/l had positive predictive value 90% and negative predictive value 90% in predicting mean GH <1.7 mug/l in the GHDC. CONCLUSIONS: The hormonal data obtained from an OGTT (mean and nadir GH) can provide comprehensive information on the status of acromegaly following surgery and can replace the GHDC cost-effectively. Furthermore, a morning fasting GH sample has an excellent positive predictive value in predicting biochemical cure and an optimal prognostic profile in predicting "safe" mean GH levels.